What does evidence-based medicine tell us about treatments for different subtypes of psoriatic arthritis? A systematic literature review on randomized controlled trials. Issue 1 (8th January 2018) - Bakirci Ureyen, Sibel; Ivory, Catherine; Kalyoncu, Umut; Karsh, Jacob; Aydin, Sibel Zehra
Abstract: Objective: PsA is a heterogeneous disease with various subtypes of joint manifestations, which can affect the homogeneity of randomized controlled trials (RCTs). The aim of this systematic literature review was to evaluate the inclusion criteria, demographics and outcomes of RCTs to see whether the whole spectrum of PsA was represented. Methods: Medline, EMBASE and Cochrane databases were screened for RCTs on the efficacy of any treatment for PsA up to 4 October 2016 to investigate the inclusion criteria, demographics, outcomes and efficacy. Results: Two thousand and sixty-eight abstracts were identified at screening; 76 articles and 52 conference proceedings were included in the final analysis. The main inclusion criteria always included the number of active joints and never axial symptoms, enthesitis nor dactylitis. Only 10 studies provided information about subtypes, of which symmetrical polyarthritis was the main subtype. Mean (s .d .) tender and swollen joints were between 7.8 and 35.8 (1.8–22.1) and between 5.2 and 25.2 (1.5–16.2), respectively. All studies had responses in joint counts as their primary outcome. Responses in enthesitis and dactylitis were usually secondary or tertiary outcomes. Response in BASDAI was among the outcomes in four studies. The comparison of efficacy in polyarticular vs oligoarticular disease was given in three studies, whereas no information was available for DIP joint disease or arthritis mutilans. Conclusion: There is evidence in the literature to guide clinicians on how to treat PsA patients with polyarticular disease, but there is a gap in knowledge about the other subtypes. Protocol registration: The study protocol is registered at PROSPERO (CRD42017053907).